Lung cancer screening eligibility and completion among adults diagnosed with lung cancer: retrospective analysis of 2024 National Health Interview Survey - Izabella Zanazanian; Angela Yin Chieh; Aarushi Madan; Franceskrista Morales; Gelareh Sadigh (Cancer Causes & Control, 2026)
Abstract Purpose Lung cancer screening using low-dose computed tomography (LDCT) is recommended for high-risk individuals, yet uptake remains low. We evaluated screening eligibility and completion among adults with lung cancer. Methods In the 2024 National Health Interview Survey, adults aged ≥ 50 years with a lung cancer diagnosis within the past 10 years were included. Eligibility at diagnosis was determined using 2021 United States Preventive Services Task Force criteria based on self-reported smoking history. LDCT completion before diagnosis was assessed. Weighted multivariable logistic regression identified factors associated with outcomes. Results 115 participants were included (weighted n = 638,702). Eligibility could not be determined for 3.5% (4/115). Among those with known eligibility, 52.3% (58/11) met screening criteria at diagnosis. Female sex (OR 0.31; 95% CI 0.12–0.77; p = 0.01) was associated with lower odds of eligibility, while non-white race showed a trend toward lower eligibility (OR 0.35; 95% CI 0.12–1.04; p = 0.06). After excluding participants who never smoked, no variables were significant. Overall, 83.6% (92/110) reported receipt of LDCT, but only 32.7% (36/110) received it before diagnosis. No variables were significantly associated with screening completion. Conclusion Among US adults with lung cancer, approximately half were screening-eligible, and only one-third underwent screening before diagnosis, highlighting gaps in both eligibility and utilization.